Os reflexos da implantação do Balanced Scorecard no desempenho organizacional: estudo de caso da Degrémont Tratamento de Águas Ltda - Lopes, Andréa Regina Ubeda (2011)
The organizational competitiveness is increasing every each day and the way the companies face these new challenges indicates its differential. The thought of this current research longs for demonstrating the importance of adopting a strategic eye through the Balanced Scorecard (BSC) and demonstrate the results it brings about to the company. With the aim of going deep in this subject, it was done a study in the company Degrémont Water Treatment Ltd which has been adopting the use of BSC since mid of 2008. By analyses of accounting demonstratives from 2005 to 2010 and structural appointment, the research demonstrates the importance of the introduction of BSC in the economic and financial results of the company when all the contributors clearly determine their strategies and goals. After analyzing the databases it was possible to verify that the mainly financial results were the raise of billing and the cut in costs and expenses. On the other hand, the results of the non financial were a better organizational culture with the commitment of the contributors with the strategies, which demonstrates that the BSC brought about quantitative and qualitative results to Degrémont Company